Statistical analysis to determine the most influential factors on traffic accidents from the driver’s point of view: A field study of a sample of drivers in Erbil Governorate - Nasreen Kakel Othman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Traffic accidents have emerged as a significant issue for society, posing a major concern for everyone. They have become a prominent problem that depletes societies of their most valuable asset, the human element. Moreover, they give rise to social and psychological issues and result in substantial financial losses. Therefore, it is necessary to pay attention and make unremitting efforts in order to reduce the percentage of victims and losses of accidents through traffic awareness and follow-up more by the traffic departments and urging the improvement of roads and the elimination of some negative phenomena that exist among motorists. The primary goal of the study was to identify the factors and reasons that contribute to the rise in traffic accidents, as perceived by drivers. To accomplish this, the researcher employed statistical methods and analyzed the data using the SPSS program. Including the method of factor analysis, which consisted of the research sample consisted of (400) drivers, as a questionnaire was prepared consisting of (30) phrases. The findings of the study indicated that the use of factor analysis reached nine main underlying factors that cause the increase in traffic accidents by (78.736), including: factors related to rough driving, factors related to the driver’s violation of traffic rules and ethics, factors related to road characteristics, factors related to deviant driving, related factors. The physical nature of the driver, factors related to road traffic regulation tools, factors related to vehicle characteristics (the vehicle), and factors related to pedestrians, factors related to adverse climatic conditions.